Monolaurin Confers a Protective Effect Against Porcine Epidemic Diarrhea Virus Infection in Piglets by Regulating the Interferon Pathway - Zhang, Qian; Yi, Dan; Ji, Changzheng; Wu, Tao; Wang, Manli; Guo, Shuangshuang; Wang, Lei; Zhao, Di; Hou, Yongqing (Frontiers in Immunology, 2022)
Porcine epidemic diarrhea virus (PEDV) has reemerged as the main pathogen of piglets due to its high mutation feature. Monolaurin (ML) is a natural compound with a wide range of antibacterial and antiviral activities. However, the role of ML in PEDV infection is still unknown. This study aimed to evaluate the effect of ML on the growth performance, intestinal function, virus replication and cytokine response in piglets infected with PEDV, and to reveal the mechanism through proteomics analysis. Piglets were orally administrated with ML at a dose of 100 mg/kg·BW for 7 days before PEDV infection. Results showed that although there was no significant effect on the growth performance of piglets, ML administration alleviated the diarrhea caused by PEDV infection. ML administration promoted the recovery of intestinal villi, thereby improving intestinal function. Meanwhile, PEDV replication was significantly inhibited, and PEDV-induced expression of IL-6 and IL-8 were decreased with ML administration. Proteomics analyses showed that 38 proteins were differentially expressed between PEDV and ML+PEDV groups, and were significantly enriched in the interferon-related pathways. This suggests ML could promote the restoration of homeostasis by regulating the interferon pathway. Overall, the present study demonstrated ML could confer a protective effect against PEDV infection in piglets, and may be developed as a drug or feed additive to prevent and control PEDV disease.